Effects of packaging and storage condition on functional properties and quality attributes of cassava flour (CVS. ‘TME 419’ AND ‘UMUCASS 36’) - Uchechukwu-Agua, Amarachi Divine (Stellenbosch : Stellenbosch University, 2015., 2015)
Thesis (MSc Food Sc)--Stellenbosch University, 2015.